47. EVALUATING THE IMPACT OF COGNITIVE IMPAIRMENT ON DAILY LIVING ACTIVITIES IN ELDERLY PATIENTS AT BACH MAI HOSPITAL'S REHABILITATION CENTER IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: (1) To describe the characteristics of cognitive impairment in elderly patients undergoing treatment at Bach Mai Hospital's Rehabilitation Center in 2025; (2) To analyze the impact of cognitive impairment on daily living activities in elderly patients at Bach Mai Hospital's Rehabilitation Center in 2025.Research methods: A descriptive cross-sectional study was conducted at Bach Mai Hospital's Rehabilitation Center.Research results: The study revealed that 62.5% of elderly patients at the center experienced cognitive impairment, primarily of a mild degree. Notably, the 60-69 age group showed the highest prevalence of cognitive impairment, reflecting a trend of the condition affecting younger elderly individuals. Furthermore, a clear correlation emerged: the more severe the cognitive impairment, the higher the level of dependence in daily activities, with 70% of cognitively impaired patients exhibiting severe reliance. This confirms that cognitive impairment significantly impacts the independence of elderly patients.Conclusion: Cognitive impairment has a direct and strong link with daily living function. The more cognitive impairment, the more severely the ability to perform daily activities was affected, leading to a higher level of dependence.
Keywords: Cognitive impairment; Daily living function (or Activities of Daily Living - ADLs); Elderly people (or older adults); Rehabilitation